Cobalt nitride enabled benzimidazoles production from furyl/aryl bio-alcohols and o-nitroanilines without an external H-source - Li, Chuanhui; Zhang, Li-Long; Li, Hu; Yang, Song (Frontiers of chemical science and engineering, 2023)
Benzimidazole derivatives have wide-spectrum biological activities and pharmacological effects, but remain challenging to be produced from biomass feedstocks. Here, we report a green hydrogen transfer strategy for the efficient one-pot production of benzimidazoles from a wide range of bio-alcohols and o -nitroanilines enabled by cobalt nitride species on hierarchically porous and recyclable nitrogen-doped carbon catalysts (Co/CN x -T, T denotes the pyrolysis temperature) without using an external hydrogen source and base additive. Among the tested catalysts, Co/CN x -700 exhibited superior catalytic performance, furnishing 2-substituted benzimidazoles in 65%–92% yields. Detailed mechanistic studies manifest that the coordination between Co 2+ and N with appropriate electronic state on the porous nitrogen-doped carbon having structural defects, as well as the remarkable synergetic effect of Co/N dual sites contribute to the pronounced activity of Co/CN x -700, while too high pyrolysis temperature may cause the breakage of the catalyst Co-N bond to lower down its activity. Also, it is revealed that the initial dehydrogenation of bio-alcohol and the subsequent cyclodehydrogenation are closely correlated with the hydrogenation of nitro groups. The catalytic hydrogen transfer-coupling protocol opens a new avenue for the synthesis of N -heterocyclic compounds from biomass.